A CRITICAL ANALYSIS OF THE ESTABLISHMENT OF THE CATHOLIC DIOCESES IN INDIA IN THE WAKE OF THE UNIVERSAL JURISDICTION OF THE ORIENTAL CHURCHES - Kureethara, Joseph Varghese (Asian Horizons, 2014)
Christ as the perfect revelation of God the Father, established the Church so that it continues and spreads His revelation. After his Ascension, his Apostles and disciples and their successors zealously continued his mission of revealing God. The command given by Christ was to “go, and teach all nations” (Mt 28:19). Although Jesus settled the dispute among his Apostles about who the greatest among them was (Lk 9:46), as an institution of human beings, the issue of supremacy always surfaced among Christians. After the reestablishment of the Church as a respectable organization from the fourth century, the Roman Church exerted its control over other Churches in every aspect. As an Apostolic Church, the Church of St Thomas Christians in India was far away from the direct control of other Churches for a very long time. While maintaining its Catholicity, it preserved its unique expressions of faith in Liturgy, Law and Life. The great colonial and missionary enterprises from the fifteenth century and the accompanied lusitinization efforts had its severest impact among the St Thomas Christians of India. A seemingly well laid out plan by the Roman Church effected in it losing the pan-India jurisdiction, right to evangelization and self governance.